2018
DOI: 10.3390/geosciences8010020
|View full text |Cite
|
Sign up to set email alerts
|

Submarine Depositional Terraces at Salina Island (Southern Tyrrhenian Sea) and Implications on the Late-Quaternary Evolution of the Insular Shelf

Abstract: Abstract:The integrated analysis of high-resolution multibeam bathymetry and single-channel seismic profiles around Salina Island allowed us to characterize the stratigraphic architecture of the insular shelf. The shelf is formed by a gently-sloping erosive surface carved on the volcanic bedrock, mostly covered by sediments organized in a suite of terraced bodies, i.e. submarine depositional terraces. Based on their position on the shelf, depth range of their edge and inner geometry, different orders of terrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
(69 reference statements)
0
13
0
1
Order By: Relevance
“…Going further back in time, the SDTs recognized above the insular shelves of Salina are associated with relative sea level stillstands during the post‐LGM transgressive stage (Casalbore et al, , ), but they cannot easily be matched with specific points of the eustatic curve in the absence of reliable age constraints. However, some SDTs associated with the LGM in the south‐eastern submarine sector of Salina Island suggest a localized subsidence during the last 20 ka (Casalbore et al, ). This subsidence is more likely related to tectonic activity along NE–SW striking normal and transtensive faults forming graben‐like structures along the channel separating Salina from the nearby Lipari Island (Ventura et al, ), and it thus does not influence the generalized uplift suggested for Salina during the last deglaciation.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Going further back in time, the SDTs recognized above the insular shelves of Salina are associated with relative sea level stillstands during the post‐LGM transgressive stage (Casalbore et al, , ), but they cannot easily be matched with specific points of the eustatic curve in the absence of reliable age constraints. However, some SDTs associated with the LGM in the south‐eastern submarine sector of Salina Island suggest a localized subsidence during the last 20 ka (Casalbore et al, ). This subsidence is more likely related to tectonic activity along NE–SW striking normal and transtensive faults forming graben‐like structures along the channel separating Salina from the nearby Lipari Island (Ventura et al, ), and it thus does not influence the generalized uplift suggested for Salina during the last deglaciation.…”
Section: Discussionmentioning
confidence: 72%
“…Going further back in time, the SDTs recognized above the insular shelves of Salina are associated with relative sea level stillstands during the post‐LGM transgressive stage (Casalbore et al, , ), but they cannot easily be matched with specific points of the eustatic curve in the absence of reliable age constraints. However, some SDTs associated with the LGM in the south‐eastern submarine sector of Salina Island suggest a localized subsidence during the last 20 ka (Casalbore et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such Pliocene–Pleistocene calcarenites in the Mediterranean area are common on storm‐dominated steep‐gradient margins (Massari & Chiocci, 2006). In the Aeolian archipelago, clinoform bodies have been reported around all islands, likely formed by downwelling offshore currents formed during storms (Chiocci & Romagnoli, 2004; Casalbore et al , 2018). All of these examples show similar deposits to the wedges of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Also on Oahu, Tsutsui et al (1987) reported offshore transport of shelf sand during the passage of a hurricane. Similarly, the presence of thick sand bodies on the bank margins of the Little and Great Bahama Bank is explained by offshore transport of carbonate sands during storms (Hine et al, 1981;Chabaud et al, 2016). Lower Pleistocene calcarenitic clinoform bodies in Rhodes, Greece, are referred to storms in a regressive regime of a highstand system tract or a forced regression (Hanken et al, 1996;Hansen, 1999).…”
Section: General Remarksmentioning
confidence: 99%